Efektivitas Peran Lurah dalam Pemberdayaan Masyarakat: Studi di Kelurahan Dara Kecamatan Rasanae Barat Kota Bima - Mohammad Irfan; Salahuddin Salahuddin (Lembaga Pengembangan Kinerja Dosen, 2026)
The urban village (kelurahan) is the government unit that interacts directly with the community and holds a strategic position in promoting development and community empowerment. The village head (Lurah) plays an essential role in encouraging public participation, coordinating development programs, and fostering community development. This study aims to analyze the role of the Lurah of Dara Urban Village in community empowerment and to identify the factors that support and hinder the effectiveness of this role. The study employed a qualitative descriptive approach and was conducted in Dara Urban Village, Rasanae Barat District, Bima City. Data were collected through interviews, observations, and documentation, and were analyzed descriptively using data reduction, data display, and conclusion drawing. The findings indicate that the Lurah’s role in community empowerment is carried out through three main functions: planning, implementation, and supervision. During the planning stage, the Lurah involved village officials, community members, and the Community Empowerment Institution (LPM) in formulating development agendas. During the implementation stage, the Lurah performed governmental, developmental, and community development functions through program coordination, participatory development, and support for community economic activities. During the supervision stage, the Lurah monitored government administration, physical development projects, and community economic development programs. The effectiveness of these roles was supported by internal coordination, community participation, the support of the LPM, and the Lurah’s field leadership. However, it was constrained by limited personnel, inadequate infrastructure, the limited capacity of government staff, and the relatively low educational level of some community members. This study highlights that community empowerment at the urban village level requires strong leadership from the Lurah, accompanied by adequate institutional and social support.